Genetic Diversity Studies in Twenty Accessions of Hot Pepper (Capsicum Spp L.) In Ghana. - Doku, S.K. (University of Ghana, 2015)
Twenty (20) accessions of hot pepper (Capsicum spp L.) were collected from eight geographical regions of Ghana for genetic diversity studies. The objective was to assess genetic relationship among them using phenotypic and molecular traits and to evaluate their elemental composition. A replicated field experiment was conducted to assess their genetic diversity based on 13 quantative traits and 22 qualitative traits using the IBPGR descriptor list for Capsicum. Confirmation of their identities was done using 10 SSR markers. The accessions were also evaluated for macro, micro and trace elements in their fresh fruits using the Instrumental Neutron Activation Analysis (INAA). Five essential macro elements (Ca, Cl, K, Mg and Na), two micro elements (Al and Mn) and one trace element (Br) were detected by INAA. Results from the agromorphological study revealed that accession Wes 01 had the widest stem width, matured leaf width, high fruit set but late maturing. Nor 03 was early maturing and had high fruit set, but also possesssed the highest number of seeds per fruit. Fruit weight, fruit width, fruit length and plant canopy width, recorded the highest variabilities with 66.191; 53.24; 49.32; and 32.42 coefficients of variation (CVs), respectively. Few traits such as plant canopy width, plant height, fruit length, mature leaf length and number of seeds per fruit contributed substantially to total genetic variance as revealed by the principal component analysis (PCA). A dendrogram generated using morphological traits grouped accessions into cultivated and wild genotypes of pepper and all the accessions were identified as separate entities with no duplications. Strong correlation was recorded between plant canopy width and plant height, mature leaf length and mature leaf width, and also fruit weight and fruit width and fruit length. Negative correlation was however, observed between fruit length and days to 50% fruiting and flowering. All three accessions from the Northern Region, Nor-01, Nor-02 and Nor-03, as well as Vol-01 from the Volta Region recorded high amount of Sodium in their fruit samples. Genetic analysis of the structure of the population showed close resemblance among the accessions with a high genetic identity coefficient of 0.975 between populations 1 and 2. A rather short genetic distance was recorded evidenced by high outcrossing rate of 0.72. Accessions Wes 01 and Nor 03 may be recommended for improvement for the export market.
Thesis (MPhil) - University of Ghana, 2015